2006
DOI: 10.1002/chem.200501468
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Self‐Assembly and Self‐Organization of Hydrogen‐Bonded Supramolecular Tapes

Abstract: Self-assembling building blocks that are readily functionalizable and capable of achieving programmed hierarchical organization have enabled us to create various functional nanomaterials. We have previously demonstrated that N,N'-disubstituted 4,6-diaminopyrimidin-2(1 H)-one (DAP), a guanine-cytosine hybridized molecule, is a versatile building block for the creation of tapelike supramolecular polymer species in solution. In the current study, DAP was functionalized with azobenzene side chains. 1H NMR, UV/Vis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 119 publications
0
40
0
Order By: Relevance
“…The similar sheetlike morphologies have been reported for organogels composed of two-dimensionally organized supramolecular aggregates. 44,45 In contrast, the SEM image of 2 Á Bar displayed self-assembled structures with a grainy surface (Figure 7a). To confirm the presence of finer structures in nanoscopic scale, the surface of the xerogel of 2 Á Bar was analyzed by atomic force microscopy (AFM).…”
Section: Microscopic Structuresmentioning
confidence: 92%
“…The similar sheetlike morphologies have been reported for organogels composed of two-dimensionally organized supramolecular aggregates. 44,45 In contrast, the SEM image of 2 Á Bar displayed self-assembled structures with a grainy surface (Figure 7a). To confirm the presence of finer structures in nanoscopic scale, the surface of the xerogel of 2 Á Bar was analyzed by atomic force microscopy (AFM).…”
Section: Microscopic Structuresmentioning
confidence: 92%
“…The latter characteristic is sometimes precious for dynamic control of assembly and disassembly processes. For example, Yagai et al reported photoresponsive self-assembly using a hydrogen-bond-directed cyclic hexamer (rosette) formed between melamine and barbituric acid derivatives (figure 56) [501,502]. In their system, azobenzene was selected as a photo-isomeric unit.…”
Section: Other Small Moleculesmentioning
confidence: 99%
“…1 They have a wide range of applications in biomaterials, 2 -4 smart materials, 5,6 medicines, 7 -9 electronic devices, 10,11 and optical technologies. 12,13 Because of their highly organized nanostructures, supramolecular polymers present many advantages, such as molecular operability, cycle applicability, self-healing properties, and molecular recognition. 14 However, until now, most supramolecular polymer filaments are not free standing, which may bring out poor mechanical properties and may limit their applications.…”
Section: Introductionmentioning
confidence: 99%